Ethical research conducted in solar and wind energy towards sustainable development in South Africa - Setshedi, Irene Glorina (My University, 2015)
The research aims to determine whether ethics are applied in the research and implementation of renewable energy projects in South Africa. It explores whether researchers involved in the renewable energy environment are transparent about all their findings. The research also uncovers the sustainability of renewable energy and it explores whether there is holistic communication with respect to renewable energy between all the relevant stakeholders. . A qualitative approach was used to conduct the study. Twenty participants who are professionals in the renewable energy environment were interviewed. The participants range from researchers, electricity grid managers and the bulk of the participants were engineers. The recordings from the interviews were transcribed to enable data analysis. Ethics in renewable energy research were found to be in existence to a large extent. The research community that participated in the research indicated that it is their responsibility to divulge all their findings and communicate all the information to all stakeholders. Renewable energy was found to be a fossil fuel saver rather than a replacement. The implementation thereof comes at a very high cost which is contrary to the requirements of sustainability. The study found that there were unintended positive and negative consequences associated with renewable energy. The key message from this study is that government and institutions involved in renewable energy must be forthcoming about the real reasons for implementing renewable energy, the associated advantages and disadvantages and thus making communication transparent and holistic.
Keywords: Solar energy ;Wind power ;Renewable energy sources ;Sustainable development ;Energy policy -- South Africa